Personality Traits and Motivations of Chinese Adults Seeking Cosmetic Botulinum Toxin Injection - Wang C; Qian H; Zhang M; Yi C (Clinical, Cosmetic and Investigational Dermatology)
Chen Wang, Huan Qian, Mengwen Zhang, Chenggang Yi Department of Plastic Surgery, The Second Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Chenggang Yi, Department of Plastic Surgery, The Second Affiliated Hospital, School of Medicine, Zhejiang University, 88 Jiefang Road, Hangzhou, Zhejiang, People’s Republic of China, Tel + 86-571-87784558, Fax + 86-571-87215882, Email yichg@zju.edu.cnBackground: Cosmetic Botulinum toxin (BoTx) injection has become a popular trend. There is evidence that beauty seekers improve their self-esteem and psychological state through BoTx injection. However, the personality traits in Chinese patients with cosmetic injections have not yet been investigated.Objective: This study aimed to investigate the motivations and personality profiles of patients seeking cosmetic BoTx injections using the Eysenck Personality Questionnaire (EPQ).Methods: The present study used a cross-sectional design, and was conducted with a sample of 195 randomly selected patients seeking BoTx treatment. All participants completed the EPQ. We also provide options listed to explore patients’ motivations for seeking treatment. The demographic information was collected and analysed.Results: A total of 195 patients were enrolled, with a mean age of 33.09 ± 8.70 years. Of the 195 participants, 177 (90.77%) were women and 18 (9.23%) were men. The mean age of the participants was 33.09 ± 8.70 years, and the majority (74.36%) had a bachelor’s degree or higher. We investigated three injection options, including lower facial contour treatment, anti-aging wrinkle injection, and body slimming injection. The EPQ of all participants showed higher E and N scores, but lower P and L scores compared to the norms. The participants age below 30 of lower facial contour injection had significantly higher P scores (p=0.048) and N scores (p=0.004), while N scores of anti-aging wrinkle treatments were significantly lower (p=0.013).Conclusion: Our study was the first using EPQ to depict the personality traits of Chinese adults seeking cosmetic BoTx injection. Initially, we questioned the purpose of aesthetic treatment in the Chinese population, which were more affected by psychological factors. Identifying personality traits before injection will assist physicians in providing a psychologically matched treatment plan while improving treatment satisfaction. These findings suggest that understanding patients’ personality traits can help physicians better predict treatment expectations and preferences. For example, patients with high neuroticism scores may be more anxious about treatment outcomes, so physicians can provide more detailed pre-treatment counseling and postoperative follow-up, which is crucial for improving treatment satisfaction and reducing potential medical disputes.Keywords: aesthetic treatment, botulinum toxin injection, Eysenck Personality Questionnaire, EPQ, personality traits